Abah Lukmanul Hakim Tokoh Islam Kontroversial Di Kalangan Umat Islam Indragiri Hilir Riau Pada Tahun 1970-An - A. Muthalib (Jurnal Edukasi, 2022)
This research aims to find answers to what is being questioned among the Inhil community mentioned above. This research found the answer: it turns out that a Muslim is allowed to keep a dog, as long as there is a certain need. For example, keep dogs for hunting purposes, guard livestock, and guard plants (gardens). Based on these findings, Muslims are not prohibited from keeping dogs. In fact, Islamic law is flexible; when conditions are normal (without any particular reason), keeping a dog is haram, but when conditions are not normal, then the law is permissible to keep a dog. So what Abah did was indirectly, he wanted to provide enlightenment to society in a subtle way, that in responding to every phenomenon, we should not always think in normal conditions, but we must also look at abnormal conditions and how Islamic law provides alternatives. As is known, many of our people work in the plantation sector. Therefore, we must know about this issue; otherwise, It is not impossible that the "su uzzhan" (bad thoughts) of the Inhil people towards Abah Lukman in the past will happen again in the future.